Management of inflammatory bowel disease in older persons: evolving paradigms - Kedia, Saurabh (Intest Res, 2018)
The incidence and prevalence of inflammatory bowel disease (IBD) is increasing, and considering the aging population, this number is set to increase further in the future. The clinical features and natural history of elderly-onset IBD have many similarities with those of IBD in younger patients, but with significant differences including a broader differential diagnosis. The relative lack of data specific to elderly patients with IBD, often stemming from their typical exclusion from clinical trials, has made clinical decision-making somewhat challenging. Treatment decisions in elderly patients with IBD must take into account age-specific concerns such as comorbidities, locomotor and cognitive function, and polypharmacy, to set realistic treatment targets in order to enable personalized treatment and minimize harm. Notwithstanding paucity of clinical data, recent studies have provided valuable insights, which, taken together with information gleaned from previous studies, can broaden our understanding of IBD. These insights may contribute to the development of paradigms for the holistic and, when possible, evidence-based management of this potentially vulnerable population and are the focus of this review.